APPLICATION OF PICTURE AND PICTURE COOPERATIVE LEARNING MODELS TO IMPROVE SPEAKING ABILITY CLASS X TKJ STUDENTS 2 SMK MUHAMMADIYAH 1 PEKANBARU - Isnaniah Isnanih (Universitas Negeri Medan, 2021)
Abstract: Application Of Picture And Picture Cooperative Learning Models To Improve Speaking Ability Class X TKJ Students 2 Smk Muhammadiyah 1 Pekanbaru. This research was conducted with the aim to determine the effect of the application of the picture and picture cooperative learning model to improve the speaking ability of class X TKJ 2 students at SMK Muhammadiyah 1 Pekanbaru, of the total 28 students there were 9 students or 32.14% who had not reached The minimum completeness criteria (KKM), while those who had reached the minimum completeness criteria were 19 students or 67.86%. This research is a class action research or class action research by applying the picture and picture cooperative learning model which is conducted in two cycles, in which each cycle consists of 4 stages, namely the planning stage, the implementation stage, the observation stage and the reflection stage. The subjects of this study were 28 students of class X TKJ 2 SMK Muhammadiyah 1 Pekanbaru. The instrument used in data collection was a learning outcome test. The results showed that the students' speaking ability had increased by using the picture and picture cooperative learning model. In the initial data before being given the action, it was seen that the class average score of the students' speaking ability was 71.2 and the percentage of completeness was only 67.86%. In the action cycle I with the application of the picture and picture cooperative learning model, it was obtained that the class average score was 81.45 with the presentation of completeness increased, namely to be 89.29%, while in the second cycle action with the application of the cooperative learning model picture and picture the students' speaking ability experienced the increase in the class average score, namely the bias reached 85.00 with the presentation of completeness also increased, namely reaching 100%. Keywords : Classroom Action Research, Speaking Skills, Cooperative Picture and Picture Abstrak: Penerapan Model Pembelajaran Kooperatif Picture And Picture Untuk Meningkatkan Kemampuan Berbicara Peserta Didik Kelas X TKJ 2 Smk Muhammadiyah 1 Pekanbaru. Penelitian ini dilakukan dengan tujuan untuk mengetahui pengaruh penerapan model pembelajaran kooperatif picture and picture untuk meningkatkan kemampuan berbicara peserta didik kelas X TKJ 2 di SMK Muhammadiyah 1 Pekanbaru, dari jumlah 28 orang peserta didik terdapat 9 orang peserta didik atau 32,14 % yang belum mencapai Kriteria Ketuntasan Minimum (KKM) sedangkan yang sudah mencapai Kriteria Ketuntasan Minimum sebanyak 19 orang peserta didik atau 67,86 %. Penelitian ini merupakan penelitian tindakan kelas atau class action research dengan menerapkan model pembelajaran kooperatif picture and picture yang dilakukan dalam dua siklus, dimana dalam setiap siklus terdiri dari 4 tahapan yaitu tahap perencanaan, tahap pelaksanaan, tahap pengamatan dan tahap refleksi. Subjek penelitian ini adalah peserta didik kelas X TKJ 2 SMK Muhammadiyah 1 Pekanbaru yang berjumlah 28 orang peserta didik. Instrumen yang digunakan dalam pengumpulan data adalah tes hasil belajar. Hasil penelitian menunjukan bahwa kemampuan berbicara peserta didik mengalami peningkatan dengan menggunakan model pembelajaran kooperatif picture and picture. Pada data awal sebelum diberikan tindakan terlihat bahwa nilai rata-rata kelas kemampuan berbicara peserta didik 71, 2 dan presentase ketuntasan hanya 67, 86 %. Pada tindakan siklus I dengan penerapan model pembelajaran kooperatif picture and picture diperoleh nilai rata-rata kelas 81,45 dengan presentasi ketuntasan mengalami peningkatan yaitu menjadi 89,29 % sedangkan pada tindakan siklus II dengan penerapan model pembelajaran kooperatif picture and picture kemampuan berbicara peserta didik mengalami kenaikan pada nilai rata-rata kelas yaitu bias mencapai 85,00 dengan presentasi ketuntasan juga mengalami peningkatan yaitu mencapai 100 %. Kata Kunci : Penelitian Tindakan Kelas, kemampuan berbicara, Kooperatif Picture da Picture